2019
DOI: 10.6007/ijarbss/v9-i9/6378
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualising Personal Resources on Career Adaptability

Abstract: The literature on career adaptation is vast and based on a range of different measurement approaches. The present paper aims to understand the influence of personal resources on career adaptability in terms of concern, control, curiosity, and confidence among graduates. This study is based on an extensive review of past research on personal resources and career adaptability using the career construction theory. To conduct the literature review, we used keywords such as personal resources, emotional intelligenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 29 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…Managing own emotions predicted career adaptability to a greater extent than the other sub-dimensions of emotional intelligence, which implies that individuals in the Water and Sanitation Department possess the ability and the readiness to respond to change. However, research has shown that general emotional intelligence alone is not sufficient to achieve success in life as both career adaptability and managing own emotions are self-regulatory strategies that serve as important psychosocial resources in both personal and environment interaction (Le, Hamzah, & Omar, 2019;Savickas & Porfeli, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Managing own emotions predicted career adaptability to a greater extent than the other sub-dimensions of emotional intelligence, which implies that individuals in the Water and Sanitation Department possess the ability and the readiness to respond to change. However, research has shown that general emotional intelligence alone is not sufficient to achieve success in life as both career adaptability and managing own emotions are self-regulatory strategies that serve as important psychosocial resources in both personal and environment interaction (Le, Hamzah, & Omar, 2019;Savickas & Porfeli, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The workplace challenges require an individual to take a holistic view of his or her surroundings and to be prepared for unforeseeable events. Individuals' strength is critical for thriving in challenging work environments (Jiang, 2017;Le et al, 2019). To enable an individual for an unprecedented work environment, the concept of person-environment fit should be applied.…”
Section: The Influence Of Personal Resources On Career Adaptabilitymentioning
confidence: 99%
“…Individuals with abilities and skills find the ideal workplace to establish a career life path (Shabeer et al, 2019;Shen et al, 2018). Career mobility is accepted and practiced in today's dynamic workplace culture, enabling individuals to strategize and maintain their values (Le et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations